Virtual freedom : how to work with virtual staff to buy more time, become more productive, and build your dream business - Ducker, Chris (Dallas, TX : BenBella Books, 2014)
Entrepreneurs often suffer from superhero syndrome - the misconception that to be successful, they must do everything themselves. Not only are they the boss, but also the salesperson, HR manager, copywriter, operations manager, online marketing guru, and so much more. Its no wonder why so many people give up the dream of starting a business - its just too much for one person to handle. But outsourcing expert and Virtual CEO, Chris Ducker knows how you can get the help you need with resources you can afford. Small business owners, consultants, and online entrepreneurs don't have to go it alone when they discover the power of building teams of virtual employees to help run, support, and grow their businesses. 'Virtual Freedom: How to Work with Virtual Staff to Buy More Time, Become More Productive, and Build Your Dream Business' is the step-by-step guide every entrepreneur needs to build his or her business with the asset of working with virtual employees. Focusing on business growth, Ducker explains every detail you need to grasp, from figuring out which jobs you should outsource to finding, hiring, training, motivating, and managing virtual assistants. With additional tactics and online resources, 'Virtual Freedom' is the ultimate resource of the knowledge and tools necessary for building your dream business with the help of virtual staff.
Contents note continued: Freedom Spotlight: Natalie Sisson, The Suitcase Entrepreneur -- Section Seven Time to Get Started -- Your First Six Months -- Conclusion -- Bonus Section: Top 10 Virtual Team-Building Mistakes (and How to Avoid Them!).
Includes bibliographical references and index.
Keywords: Virtual reality in management; Virtual work teams -- Management; Virtual reality in management; Virtual work teams -- Management